Biomineralisation performance of bacteria isolated from a landfill in China - Rajasekar, A.; Wilkinson, S.; Sekar, R.; Bridge, J.; Medina-Roldán, E.; Loo Chin Moy, Charles (N R C Research Press, 2018)
© 2018, Canadian Science Publishing. All rights reserved. We report an investigation of microbially induced carbonate precipitation by seven indigenous bacteria isolated from a landfill in China. Bacterial strains were cultured in a medium supplemented with 25 mmol/L calcium chloride and 333 mmol/L urea. The experiments were carried out at 30 °C for 7 days with agitation by a shaking table at 130 r/min. Scanning electron microscopic and X-ray diffraction analyses showed variations in calcium carbonate polymorphs and mineral composition induced by all bacterial strains. The amount of carbonate precipitation was quantified by titration. The amount of carbonate precipitated in the medium varied among isolates, with the lowest being Bacillus aerius rawirorabr15 (LC092833) precipitating around 1.5 times more carbonate per unit volume than the abiotic (blank) solution. Pseudomonas nitroreducens szh_asesj15 (LC090854) was found to be the most efficient, precipitating 3.2 times more carbonate than the abiotic solution. Our results indicate that bacterial carbonate precipitation occurred through ureolysis and suggest that variations in carbonate crystal polymorphs and rates of precipitation were driven by strain-specific differences in urease expression and response to the alkaline environment. These results and the method applied provide benchmarking and screening data for assessing the bioremediation potential of indigenous bacteria for containment of contaminants in landfills.